STRATEGI DIGITAL MARKETING MELALUI INSTAGRAM OLEH CV. ELECTRA DIAMOND - Sujaya, Kadek Bagus Wira; Kusuma Negara, Indah Suprabawati (Institut Agama Hindu Negeri Gde Pudja Mataram, 2024)
This research aims to determine the digital marketing management carried out by CV. Electra Diamond; obstacles faced by CV. Electra Diamond in doing digital marketing on Instagram; Instagram digital marketing strategy carried out by CV. Electra Diamond in maintaining its business to be sustainable. To find out this, researchers used marketing theory and digital marketing theory. This research uses descriptive qualitative research methods, with data collection techniques in the form of observation, interviews and documentation. The results of this research are (1) digital marketing management carried out by CV. Electra Diamond is very good because it can be seen from the way goods are produced, looking at fashion products that are trending among the public, CV. Electra Diamond promotes its products; (2) obstacles faced by CV. Electra Diamond includes digital obstacles such as a decrease in the number of likes and views on content that has been uploaded, obstacles in carrying out advertising which takes a long time; and (3) digital marketing strategies used by CV. Electra Diamond is an event support and sponsorship strategy via Instagram so that it is well known to the public.